Ternary composite catalytic material as well as preparation method and application thereof
By introducing oxygen defects into bismuth vanadate and titanium dioxide and combining them with active metals to form a ternary composite catalytic material, the problems of low separation efficiency of photogenerated carriers and complex synthesis methods in the prior art are solved, and efficient ammonia decomposition and hydrogen production reaction are achieved.
Patent Information
- Application Number
- CN202311267611.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The prior art has low separation efficiency in the preparation of bismuth vanadate-based heterojunction composite systems, lacks catalytic activity centers, and is complex in synthesis, so it is not suitable for hydrogen production applications.
Using ternary composite catalytic materials, including bismuth vanadate, titanium dioxide and active metals, the oxygen defects are introduced into bismuth vanadate and/or titanium dioxide, and the active metal is introduced into the oxygen defect content by introducing oxygen defects in bismuth vanadate and/or titanium dioxide, and the active metal is calcined under a reducing atmosphere to regulate the oxygen defect content.
It significantly improves the efficiency of hydrogen production in ammonia decomposition, enhances photocatalytic activity, simplifies the preparation process, and is suitable for hydrogen production applications in ammonia decomposition.
Smart Images

Figure CN119733496A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalysis technology, and in particular to a ternary composite catalytic material and a preparation method and application thereof. Background Art
[0002] Since the 21st century, clean energy represented by hydrogen energy has developed rapidly. At the same time, the use of renewable energy such as solar energy and wind energy to drive hydrogen production reactions has received increasing attention from researchers. Currently, the commonly used catalytic conversion pathways mainly include thermal catalysis, photocatalysis and electrocatalysis. Traditional thermal catalytic methods have high energy consumption and are not conducive to large-scale applications. The use of solar energy to assist the catalytic process to achieve hydrogen production is expected to reduce dependence on fossil fuels. Ammonia is a traditional bulk chemical with a mass hydrogen content of 17.6% and high energy density. At the same time, ammonia is easy to liquefy, store and transport, and only produces hydrogen and nitrogen during the decomposition process, with no carbon emissions. Therefore, ammonia is a potential liquid hydrogen storage medium, which is expected to alleviate the problems of uneven regional distribution of hydrogen energy and difficulties in large-scale transportation.
[0003] Patent application CN112473747A discloses a method for preparing and using an ultra-thin two-dimensional metal phthalocyanine / bismuth vanadate heterojunction photocatalyst regulated by gold nanoparticles, which relates to a method for preparing and using a photocatalyst. This application solves the problem of low efficiency of photogenerated carrier separation and lack of catalytic active centers in the prior art for preparing bismuth vanadate-based heterojunction composite systems.
[0004] Patent application CN110387737A discloses a method for preparing a graphene-titanium dioxide-bismuth vanadate photocatalytic functional fabric, as follows: (1) subjecting the pre-treated fabric to plasma treatment; (2) immersing the fabric treated with plasma in step 1 in a graphene oxide dispersion, and then curling the fabric after extrusion and wrapping it with a polyethylene film, and treating it with microwaves; (3) immersing the fabric treated with microwaves in step 2 in a titanium dioxide hydrosol, and then subjecting the fabric to plasma treatment after extrusion, and then subjecting it to ultraviolet irradiation treatment; (4) immersing the fabric treated in step (3) in a bismuth vanadate sol, and then curling the fabric after extrusion and wrapping it with a polyethylene film, and then subjecting it to microwave treatment again, and then washing and drying it to obtain a graphene-titanium dioxide-bismuth vanadate photocatalytic functional fabric. However, the synthesis method of this system is relatively complicated and is not suitable for the application of ammonia decomposition to hydrogen production. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a ternary composite catalytic material and a preparation method and application thereof. The ternary composite catalytic material can greatly improve the efficiency of ammonia decomposition.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a ternary composite catalytic material, wherein the catalytic material includes bismuth vanadate, titanium dioxide and an active metal, and the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper; wherein bismuth vanadate and / or titanium dioxide contain oxygen defects, and the total content of oxygen defects in the catalytic material is not less than 2%.
[0007] Preferably, in the catalytic material, both bismuth vanadate and titanium dioxide contain oxygen defects.
[0008] Preferably, the total content of oxygen defects in the catalytic material is 2-10%, more preferably 5-8%.
[0009] A second aspect of the present invention provides a method for preparing a ternary composite catalytic material, wherein the method comprises the following steps:
[0010] (1) mixing a mixed solution A containing a bismuth source and an acid with a mixed solution B containing a metavanadate and an alkali to carry out a contact reaction, wherein the temperature of the contact reaction does not exceed 100° C.;
[0011] (2) mixing the contact reaction product obtained in step (1) with a titanium source and a solvent to perform a solvothermal reaction;
[0012] (3) mixing the solvent thermal reaction product obtained in step (2) with an active metal precursor, and then calcining the mixture under a reducing atmosphere to obtain a ternary composite catalytic material, wherein the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper.
[0013] The third aspect of the present invention provides a ternary composite catalytic material prepared by the preparation method described in the second aspect.
[0014] The fourth aspect of the present invention provides an application of the elementary composite catalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.
[0015] The ternary composite catalytic material provided by the present invention can increase the number of active sites of the ternary composite catalytic material to promote the activation of ammonia molecules and improve the efficiency of hydrogen production by decomposing ammonia by introducing oxygen defects in bismuth vanadate and / or titanium dioxide. At the same time, the interface contact between bismuth vanadate and titanium dioxide is close, which is conducive to further promoting the migration of photogenerated charges and improving the efficiency of hydrogen production by photocatalytic decomposition of ammonia; further, by introducing active metals as active sites, the ammonia decomposition activity is further improved.
[0016] The preparation method provided by the present invention uses an in-situ synthesis method to form a close interface contact between bismuth vanadate and titanium dioxide, introduces oxygen defects by calcination in a reducing atmosphere, and effectively controls the defect content. The preparation process is simple, has good repeatability, and is easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a transmission electron microscope image of the ternary composite catalytic material of Example 1;
[0018] Figure 2 This is the Mott-Schottky curve of the ternary composite catalytic material of Example 1. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides a ternary composite catalytic material, wherein the catalytic material includes bismuth vanadate, titanium dioxide and an active metal, and the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper; wherein bismuth vanadate and / or titanium dioxide contain oxygen defects, and the total content of oxygen defects in the catalytic material is not less than 2%.
[0021] The ternary composite catalytic material provided by the present invention, the heterojunction formed by the composite of bismuth vanadate and titanium dioxide, can increase the number of active sites of the ternary composite catalytic material by introducing oxygen defects in bismuth vanadate and / or titanium dioxide, and improve the efficiency of hydrogen production by decomposing ammonia. At the same time, the interface contact between bismuth vanadate and titanium dioxide is close, which is conducive to further promoting the migration of photogenerated charges and improving the efficiency of hydrogen production by decomposing ammonia.
[0022] In the present invention, the oxygen defect in the ternary composite catalytic material refers to the oxygen content in the ternary composite catalytic material being less than its theoretical stoichiometric content. The oxygen defect is measured by X-ray photoelectron spectroscopy analysis. The specific test conditions are: using high-resolution O1s spectrum peak fitting to determine lattice oxygen and defect oxygen signals, thereby calculating the molar percentage of oxygen defects as: defect oxygen / (defective oxygen+lattice oxygen)×100%.
[0023] The ternary composite catalytic material provided by the present invention may contain oxygen defects in bismuth vanadate, may contain oxygen defects in titanium dioxide, or both contain oxygen defects. Preferably, in the catalytic material, both bismuth vanadate and titanium dioxide contain oxygen defects. In the above preferred case, it is beneficial to further improve the efficiency of ammonia decomposition and hydrogen production of the photo-ternary composite catalytic material.
[0024] The present invention does not have any particular limitation on the oxygen defect content of bismuth vanadate and titanium dioxide, as long as the total content of oxygen defects in the ternary composite catalytic material is not less than 2%. Preferably, the total content of oxygen defects in the ternary composite catalytic material is 2-10%, and more preferably 5-8%. In the case of the above-mentioned preferred oxygen defect content, it is beneficial to increase the number of active sites in the ternary composite catalytic material and improve the efficiency of hydrogen production by decomposition of ammonia. When the oxygen defect content is too little, the number of active sites of the material is limited. When the oxygen defect content is too high, it will affect the lattice stability, resulting in a decrease in the stability of the ternary composite material and affecting its reaction activity.
[0025] In the present invention, preferably, the free carrier density of the catalytic material is greater than 10 22 cm -3 , more preferably 2×10 22 -8×10 22 cm -3 , and more preferably 3×10 22 -6×10 22 cm -3 The advantage of adopting this preferred embodiment is that it is conducive to accelerating the transport of photogenerated charges and improving the reaction efficiency. When the free carrier density is not within the above range, it has the defect of poor photogenerated charge transport performance.
[0026] In the present invention, the free carrier density refers to the density of electrons that can move freely in a semiconductor, and the free carrier density is calculated by testing the slope of the Mott-Schottky curve using an electrochemical workstation.
[0027] In the present invention, there is no particular limitation on the type of active metal, and any active metal suitable for ammonia decomposition to produce hydrogen in the art is suitable for the present invention. Preferably, the active metal is selected from iron and / or cobalt and ruthenium.
[0028] In the present invention, the selection range for the content of each component in the ternary composite catalytic material is relatively wide. Preferably, based on the total amount of the catalytic material, the content of bismuth vanadate is 20-60wt%, the content of titanium dioxide is preferably 20-60wt%, and the content of the active metal calculated as an element is 5-50wt%; further preferably, based on the total amount of the catalytic material, the content of bismuth vanadate is 30-50wt%, the content of titanium dioxide is 30-50wt%, and the content of the active metal calculated as an element is 8-20wt%.
[0029] In the present invention, the reaction efficiency of ammonia decomposition to produce hydrogen is improved by the cooperation of precious metal ruthenium and non-precious metal. Preferably, the mass ratio of ruthenium to (iron + cobalt) is 0.6-1.5:1 in terms of elements.
[0030] In the present invention, the content of each component of the ternary composite catalytic material is tested by inductively coupled plasma emission spectroscopy and X-ray photoelectron spectroscopy.
[0031] A second aspect of the present invention provides a method for preparing a ternary composite catalytic material, wherein the method comprises the following steps:
[0032] (1) mixing a mixed solution A containing a bismuth source and an acid with a mixed solution B containing a metavanadate and an alkali to carry out a contact reaction, wherein the temperature of the contact reaction does not exceed 100° C.;
[0033] (2) mixing the contact reaction product obtained in step (1) with a titanium source and a solvent to perform a solvothermal reaction;
[0034] (3) mixing the solvent thermal reaction product obtained in step (2) with an active metal precursor, and then calcining the mixture under a reducing atmosphere to obtain a ternary composite catalytic material, wherein the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper.
[0035] The preparation method provided by the present invention uses an in-situ synthesis method to form a close interface contact between bismuth vanadate and titanium dioxide, introduces oxygen defects by calcination in a reducing atmosphere, and can effectively control the defect content. The preparation process is simple, has good repeatability, and is easy to scale up for production.
[0036] In the present invention, there is no particular limitation on the preparation method of the mixed solution A. Preferably, in step (1), the mixed solution A containing a bismuth source and an acid is prepared by mixing a bismuth source with an acid.
[0037] In the present invention, there is no particular limitation on the preparation method of the mixed solution B. Preferably, in step (1), the mixed solution B containing metavanadate and alkali is prepared by mixing metavanadate and alkali.
[0038] In the present invention, the amount of the bismuth source and the metavanadate can be selected in a wide range, as long as the synthesis requirements of bismuth vanadate are met. Preferably, the molar ratio of the bismuth source calculated as bismuth element to the metavanadate calculated as vanadium element is 0.5-5:1, more preferably 0.8-1.2:1.
[0039] In the present invention, preferably, H + The molar amount of the acid in terms of OH - The molar amounts of the bases are equal.
[0040] In the present invention, preferably, in step (1), the acid is provided by an aqueous solution of the acid, and the concentration of the aqueous solution of the acid is 0.5-4 mol / L, more preferably 1-3 mol / L, for example, it can be 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L and values between any two groups.
[0041] In the present invention, the amount of the acid aqueous solution is not particularly limited, as long as it can meet the contact reaction requirements, and those skilled in the art can select it according to actual needs. Preferably, the amount of the acid aqueous solution is 200-800 mL, more preferably 350-700 mL, relative to 1 mol of the bismuth source calculated as bismuth element.
[0042] In the present invention, preferably, the alkali is provided by an aqueous solution of alkali, and the concentration of the aqueous solution of alkali is 0.5-4 mol / L, more preferably 1-3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L and values between any two groups. In the present invention, the concentration of the aqueous solution of the acid may be the same as or different from the concentration of the aqueous solution of the alkali, and the present invention has no particular limitation on this.
[0043] In the present invention, the amount of the aqueous solution of the alkali is not particularly limited, as long as it can meet the contact reaction requirements, and those skilled in the art can select it according to actual needs. Preferably, the amount of the aqueous solution of the alkali is 200-800 mL, more preferably 350-700 mL, relative to 1 mol of the metavanadate calculated as vanadium element.
[0044] In the present invention, the acid can be selected in a wide range, and conventional organic acids or inorganic acids in the art can be used, which are specifically limited in the present invention. Preferably, the acid is selected from at least one of nitric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid and hydrochloric acid, and more preferably nitric acid.
[0045] In the present invention, the specific type of the base can be selected in a wide range. Preferably, the base can be an alkali metal hydroxide, such as sodium hydroxide and / or potassium hydroxide.
[0046] In the present invention, there is no particular limitation on the specific type of bismuth source, as long as bismuth element can be provided, conventional bismuth-containing compounds in the art can be applied to the present invention. Preferably, the bismuth source is selected from at least one of bismuth nitrate, bismuth trichloride and bismuth subsalicylate.
[0047] In the present invention, there is no particular limitation on the type of metavanadate. Preferably, the metavanadate is selected from at least one of sodium metavanadate, potassium metavanadate and ammonium metavanadate.
[0048] In the present invention, preferably, step (1) comprises: adding the mixed solution A containing the bismuth source and the acid to the mixed solution B containing the metavanadate and the alkali under stirring to carry out a contact reaction. In the present invention, there is no particular limitation on the stirring conditions, as long as the reaction can be promoted, and those skilled in the art can select according to actual needs.
[0049] In the present invention, preferably, the addition rate of the mixed solution A containing the bismuth source and the acid is 0.5-5 mL / min relative to 10 mL of the mixed solution B containing the metavanadate and the base. The above preferred embodiment has the advantage of uniform mixing of the precursor solution.
[0050] In the present invention, preferably, in step (1), the conditions of the contact reaction include: the temperature is room temperature-80°C, for example, it can be room temperature, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C and values between any two groups; the time is 0.5-24h, for example, it can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h and values between any two groups. In the present invention, the contact reaction in step (1) can be carried out under relatively mild reaction conditions, and the reaction temperature does not exceed 100°C, preferably at room temperature-80°C. In the present invention, "room temperature" refers to 25±5°C. The inventors of the present invention have found in their research that bismuth vanadate synthesized at a lower contact reaction temperature has uniform particle size, which helps to enhance the contact strength between in-situ synthesized titanium dioxide and bismuth vanadate, and helps to control the oxygen defect content. In the prior art, the preparation of bismuth vanadate by precipitation method often needs to be carried out under high temperature and high pressure conditions, and the reaction temperature is generally above 150°C.
[0051] In the present invention, the product obtained in step (1) is mixed with a titanium source and a solvent to perform a solvothermal reaction, thereby synthesizing titanium dioxide in situ on a bismuth vanadate substrate, so that a close interface contact is formed between the bismuth vanadate and the titanium dioxide. In the present invention, there is no particular limitation on the type of titanium source, as long as it can provide titanium. Preferably, the titanium source is a titanium-containing compound, preferably selected from at least one of tetrabutyl titanate, titanium sulfate and titanium tetrachloride. The above preferred embodiment is adopted to promote the migration of photogenerated charges and improve the efficiency of hydrogen production by decomposition of ammonia.
[0052] In the present invention, step (1) further comprises: subjecting the contact reaction product to solid-liquid separation. The solid-liquid separation can be carried out using conventional operation methods and conditions in the art, and the present invention has no particular limitation thereto. For example, solid-liquid separation can be carried out using centrifugation. The solid product obtained by solid-liquid separation is used in step (2).
[0053] In the present invention, the "solvothermal reaction" refers to a solvothermal reaction in a broad sense: a reaction of the original mixture at a certain temperature and autogenous pressure of the solution in the presence of water or a non-aqueous solvent in a closed system such as an autoclave. It is understood that in the present invention, the solvothermal reaction solution system depends on the type of the solvent and does not necessarily contain water.
[0054] In the present invention, there is no particular limitation on the specific type and amount of the solvent in step (2), as long as it can help disperse the contact reaction product obtained in step (1) and the titanium source, conventional solvents in the art are suitable for the present invention. In order to further improve the dispersion effect of the titanium source and improve the bonding strength of the in-situ synthesized titanium dioxide, preferably, the solvent is an alcohol, preferably a monohydric alcohol and / or a polyhydric alcohol, more preferably at least one of a C1-C10 monohydric alcohol, a dihydric alcohol and a trihydric alcohol, preferably at least one of ethanol, ethylene glycol, n-propanol, isopropanol, 1,2-propylene glycol, 1,3-propylene glycol and glycerol, more preferably at least one of ethanol, isopropanol and glycerol.
[0055] In the present invention, preferably, in step (2), the conditions of the solvent thermal reaction include: a temperature of 90-200°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C and values between any two groups; a time of 12-48h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h and values between any two groups.
[0056] In the present invention, preferably, in step (3), the active metal is selected from iron and / or cobalt and ruthenium.
[0057] In the present invention, there is no particular limitation on the type of active metal precursor, as long as it can provide each active metal element. Preferably, in step (3), the active metal precursor is selected from soluble compounds of each active metal, preferably at least one of nitrates, chlorides and sulfates of each active metal, and the present invention does not specifically limit its specific type.
[0058] In the present invention, the active metal is introduced by mixing, which is conducive to close contact between the active metal and titanium dioxide and / or bismuth vanadate. Preferably, in step (3), the mixing is mechanical mixing and / or rotary evaporation drying, and more preferably rotary evaporation drying. Compared with the impregnation method in the prior art, the active metal has the advantage of uniform metal dispersion.
[0059] In the present invention, there is no particular limitation on the specific operation of mechanical mixing, as long as the introduction of active metals can be achieved. Those skilled in the art can select according to actual needs, for example, mechanical mixing can be performed in a ball mill.
[0060] In the present invention, preferably, in step (3), the conditions for the rotary evaporation drying include: a temperature of 70-90°C. The advantage of adopting this preferred embodiment is that the metal is evenly dispersed. In the present invention, there is no particular limitation on the specific operation mode of the rotary evaporation drying. Preferably, in step (3), the rotary evaporation drying includes dispersing the active metal precursor and the solvent thermal reaction product of step (2) in a solvent (preferably water), and then rotary evaporating and drying at 70-90°C.
[0061] In the present invention, the range of calcination conditions is relatively wide. Preferably, in step (3), the calcination conditions include: a temperature of 350-600°C, for example, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, ℃, 600℃ and values between any two groups; the time is 2-8h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h and values between any two groups; the heating rate is 2-10℃ / min, for example, it can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min and values between any two groups.
[0062] In the present invention, in order to further reduce the oxygen defect content in the catalytic material, preferably, the flow rate of the reducing atmosphere is 10-80 mL / min, more preferably 20-60 mL / min, for example, it can be 10 mL / min, 20 mL / min, 25 mL / min, 30 mL / min, 35 mL / min, 40 mL / min, 45 mL / min, 50 mL / min, 55 mL / min, 60 mL / min and values between any two groups.
[0063] In the present invention, preferably, the reducing atmosphere comprises H2 and an optional inert gas. In the present invention, there is no particular limitation on the type of inert gas, such as nitrogen, argon, or neon.
[0064] In the present invention, preferably, based on the total volume of the reducing atmosphere, the total content of H2 is 5-100 volume%, more preferably 10-50 volume%, for example, 10 volume%, 15 volume%, 20 volume%, 25 volume%, 30 volume%, 35 volume%, 40 volume%, 45 volume%, 50 volume%.
[0065] In the present invention, the defect content can be effectively controlled by adjusting the calcination time, temperature and reducing atmosphere concentration, thereby increasing the number of active sites and improving the efficiency of hydrogen production by decomposing ammonia.
[0066] In the present invention, step (3) further comprises: solid-liquid separation, washing and drying of the product obtained by the calcination. The present invention has no particular limitation on the specific conditions of the solid-liquid separation, washing and drying, and they can all be carried out in a conventional manner in the art.
[0067] In the present invention, preferably, the amounts of the bismuth source, the titanium source and the active metal precursor are such that in the prepared catalytic material, the content of bismuth vanadate is 20-80wt%, the content of titanium dioxide is 20-80wt%, and the content of the active metal in terms of element is 5-20wt%; further preferably, based on the total amount of the catalytic material, the content of bismuth vanadate is 30-50wt%, the content of titanium dioxide is 30-50wt%, and the content of the active metal in terms of element is 8-20wt%.
[0068] In the present invention, preferably, the amount of the active metal precursor used is such that in the prepared catalytic material, the mass ratio of ruthenium to (iron + cobalt) is 0.6-1.5:1, calculated as elements.
[0069] The third aspect of the present invention provides a ternary composite catalytic material prepared by the preparation method described in the second aspect. The ternary composite catalytic material has the properties of the ternary composite catalytic material described in the first aspect.
[0070] The fourth aspect of the present invention provides an application of the ternary composite catalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.
[0071] In the present invention, preferably, the reaction raw material ammonia is provided by an ammonia aqueous solution, and the concentration of the ammonia aqueous solution is 0.01-0.1 mol / L.
[0072] In the present invention, there is no particular limitation on the conditions of the ammonia decomposition hydrogen production reaction. Preferably, the conditions of the ammonia decomposition hydrogen production reaction include: a reaction temperature of 0-40°C, and an amount of the ternary composite catalyst material of 0.05-0.5g relative to 0.01mol of ammonia aqueous solution.
[0073] The present invention will be described in detail below through examples.
[0074] In the following examples, unless otherwise specified, all raw materials used were purchased from commercial sources.
[0075] In the following examples, "room temperature" refers to 25±5°C.
[0076] In the following examples, the content of each component of the ternary composite catalytic material is measured by inductively coupled plasma emission spectroscopy and X-ray photoelectron spectroscopy.
[0077] Example 1
[0078] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0079] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to a solvent thermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried;
[0080] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material. Figure 1 This is the transmission electron microscope image of the ternary composite material. It can be seen that the sample exists in the form of nanoparticles and the intercrystalline dislocation is obvious. Figure 2 It is the Mott-Schottky curve test result of the ternary composite material. According to the free carrier density = 2e0 -1 ε -1 ε0 -1 |d(C -2 ) / dV| -1 Calculate, where e0 is the elementary charge value (1.60×10 -19 C), ε is the relative dielectric constant of the material (ε = 5.5), ε0 is the vacuum dielectric constant (8.85 × 10 -12 F m -1 ), d(C -2 ) / dV is the slope of the Mott-Schottky curve.
[0081] Example 2
[0082] (1) Weigh 74.9 g of bismuth nitrate pentahydrate in 60 mL of 1.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 18.8 g of sodium metavanadate in 60 mL of 1.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; fully stir the reaction for 1 hour and then centrifuge to recover;
[0083] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 170.4 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to a solvent thermal reaction at 100 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried;
[0084] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0085] Example 3
[0086] (1) Weighing 44.9 g of bismuth nitrate pentahydrate into 60 mL of 3.0 mol / L dilute nitric acid to prepare a mixed solution A; weighing 11.3 g of sodium metavanadate into 60 mL of 3.0 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly adding A to B at room temperature, with the addition rate of the mixed solution A being 5 mL / min relative to 10 mL of the mixed solution B; stirring the reaction thoroughly for 1 hour and then centrifuging and recovering;
[0087] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 255.7 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0088] (3) Weigh 10.3 g of ruthenium trichloride and 24.7 g of cobalt nitrate hexahydrate and the solid from step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere with a gas flow rate of 45 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0089] Example 4
[0090] (1) Weigh 89.8 g of bismuth nitrate pentahydrate in 60 mL of 1.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 22.6 g of sodium metavanadate in 60 mL of 1.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0091] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 127.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0092] (3) Weigh 20.5 g of ruthenium trichloride and the solid obtained in step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0093] Example 5
[0094] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0095] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0096] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 7 vol % H2 / Ar atmosphere with a gas flow rate of 20 mL / min, a calcination temperature of 350° C., a calcination time of 2 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0097] Example 6
[0098] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0099] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0100] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 70% by volume H2 / Ar atmosphere with a gas flow rate of 60 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0101] Example 7
[0102] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0103] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 180 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0104] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0105] Example 8
[0106] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0107] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0108] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and impregnate them into the above solid, then calcine them in a 15 vol% H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450°C, a calcination time of 4 h, a heating rate of 5°C per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0109] Comparative Example 1
[0110] (1) Weigh 250 mL of anhydrous ethanol and add 383.5 g of tetrabutyl titanate, stir for 1 hour, transfer to a polytetrafluoroethylene-lined reactor, and perform hydrothermal and solvothermal reaction at 90° C. for 24 hours. After the reaction, centrifuge the obtained solid, wash and dry;
[0111] (2) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid obtained in step (1) above and disperse them in 200 mL of water, dry them by rotary evaporation at 70° C., and then calcine them in a 15 vol % H2 / Ar atmosphere at a gas flow rate of 40 mL / min, a calcination temperature of 450° C., a calcination time of 4 h, a heating rate of 5° C. per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0112] Comparative Example 2
[0113] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the mixture for 1 hour, then transfer the mixture to a polytetrafluoroethylene-lined reactor, perform a hydrothermal solvothermal reaction at 90° C. for 24 hours, and centrifuge, wash and dry the obtained solid after the reaction to obtain a product C;
[0114] (2) Weigh 250 mL of anhydrous ethanol and add 191.8 g of tetrabutyl titanate, stir for 1 h, then transfer to a polytetrafluoroethylene-lined reactor, and perform a hydrothermal solvothermal reaction at 150 °C for 24 h. After the reaction, the obtained solid is centrifuged, washed, and dried to obtain product D;
[0115] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and grind and mix with products C and D, and calcine them in a 15 vol% H2 / Ar atmosphere with a gas flow rate of 40 mL / min, a calcination temperature of 450°C, a time of 4 h, a heating rate of 5°C per minute, and cool to room temperature to obtain a ternary composite catalytic material.
[0116] Comparative Example 3
[0117] (1) Weigh 67.4 g of bismuth nitrate pentahydrate in 60 mL of 2.5 mol / L dilute nitric acid to prepare a mixed solution A; weigh 16.9 g of sodium metavanadate in 60 mL of 2.5 mol / L sodium hydroxide solution to prepare a mixed solution B; slowly add A to B at room temperature, with the addition rate of the mixed solution A being 4 mL / min relative to 10 mL of the mixed solution B; stir the reaction thoroughly for 1 hour and then centrifuge to recover;
[0118] (2) The obtained product was dispersed in 250 mL of anhydrous ethanol, and 191.8 g of tetrabutyl titanate was added. After stirring for 1 h, the mixture was transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal and solvothermal reaction at 90 ° C for 24 h. After the reaction, the obtained solid was centrifuged, washed and dried.
[0119] (3) Weigh 10.3 g of ruthenium trichloride and 36.2 g of ferric nitrate nonahydrate and the solid of step (2) above and disperse them in 100 mL of water, dry them by rotary evaporation at 70°C, and then calcine them in an air atmosphere at a gas flow rate of 40 mL / min, a calcination temperature of 450°C, a time of 4 h, a heating rate of 5°C per minute, and cool them to room temperature to obtain a ternary composite catalytic material.
[0120] In the above-mentioned embodiments and comparative examples, the contents of bismuth vanadate, titanium dioxide and active metal in the ternary composite catalytic material are shown in Table 1, and the oxygen defect content and free carrier density are shown in Table 2.
[0121] Table 1
[0122] composition Example 1 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Example 2 <![CDATA[50%BiVO4-40%TiO2-5%Ru-5%Fe]]> Example 3 <![CDATA[30%BiVO4-60%TiO2-5%Ru-5%Co]]> Example 4 <![CDATA[60%BiVO4-30%TiO2-10%Ru]]> Example 5 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Example 6 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Example 7 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Example 8 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Comparative Example 1 <![CDATA[90%TiO2-5%Ru-5%Fe]]> Comparative Example 2 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]> Comparative Example 3 <![CDATA[45%BiVO4-45%TiO2-5%Ru-5%Fe]]>
[0123] Table 2
[0124] Oxygen deficiency content (%) <![CDATA[Free carrier density (10 22 cm -3 )]]> Example 1 6.0 4.6 Example 2 6.0 4.5 Example 3 7.0 3.2 Example 4 6.0 2.8 Example 5 3.5 1.2 Example 6 10.0 2.2 Example 7 2.0 1.8 Example 8 5.0 1.2 Comparative Example 1 1.5 0.8 Comparative Example 2 0.8 0.4 Comparative Example 3 0.5 1.0
[0125] Photocatalytic ammonia decomposition to produce hydrogen activity test
[0126] The obtained catalyst was used in the photocatalytic ammonia decomposition hydrogen production reaction under simulated sunlight, and the activity test was carried out using an online vacuum photocatalytic reaction device, and the light source was a 300W xenon lamp. The reaction conditions were: 0.1g catalyst, 100mL 0.1mol / L ammonia solution, and the reaction temperature was 5°C. After the reaction started, samples were taken every 1 hour to calculate the average reaction rate for 6 hours. The products were analyzed by chromatography equipped with a hydrogen flame ionization detector and a thermal conductivity cell detector, and quantified using a pre-determined standard curve. The reaction mainly produces two products, namely N2 and H2, and a small amount of O2 from the side reaction of water decomposition. The reaction results are shown in Table 3.
[0127] Table 3
[0128]
[0129] It can be seen from the above table that the catalytic material provided by the present invention has excellent ammonia decomposition activity.
[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A ternary composite catalytic material, characterized in that: The catalytic material includes bismuth vanadate, titanium dioxide and an active metal, wherein the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper; wherein bismuth vanadate and / or titanium dioxide contain oxygen defects, and the total content of oxygen defects in the catalytic material is not less than 2%.
2. The photocatalyst according to claim 1, wherein In the catalytic material, both bismuth vanadate and titanium dioxide contain oxygen defects; Preferably, the total content of oxygen defects in the catalytic material is 2-10%, more preferably 5-8%.
3. The photocatalyst according to claim 1 or 2, wherein According to the electrochemical test Mott-Schottky curve analysis, the free carrier density of the catalytic material is greater than 10 22 cm -3 , preferably 2×10 22 -8×10 22 cm -3 , more preferably 3×10 22 -6×10 22 cm -3 .
4. The photocatalyst according to any one of claims 1 to 3, wherein: The active metal is selected from iron and / or cobalt and ruthenium; Preferably, based on the total amount of the catalytic material, the content of the bismuth vanadate is 20-60wt%, the content of the titanium dioxide is 20-60wt%, and the content of the active metal in terms of element is 5-20wt%; Further preferably, based on the total amount of the catalytic material, the content of the bismuth vanadate is 30-50wt%, the content of the titanium dioxide is 30-50wt%, and the content of the active metal in terms of element is 8-20wt%; Preferably, the mass ratio of ruthenium to (iron+cobalt) is 0.6-1.5:1, calculated as elements.
5. A method for preparing a ternary composite catalytic material, wherein: The method comprises the following steps: (1) mixing a mixed solution A containing a bismuth source and an acid with a mixed solution B containing a metavanadate and an alkali to carry out a contact reaction, wherein the temperature of the contact reaction does not exceed 100° C.; (2) mixing the contact reaction product obtained in step (1) with a titanium source and a solvent to perform a solvothermal reaction; (3) mixing the solvent thermal reaction product obtained in step (2) with an active metal precursor, and then calcining the mixture under a reducing atmosphere to obtain a ternary composite catalytic material, wherein the active metal is selected from at least one of iron, ruthenium, nickel, cobalt and copper.
6. The method according to claim 5, wherein: In step (1), the mixed solution A containing a bismuth source and an acid is prepared by mixing a bismuth source with an acid; And / or, in step (1), the mixed solution B containing metavanadate and alkali is prepared by mixing metavanadate and alkali; Preferably, in step (1), the molar ratio of the bismuth source calculated as bismuth element to the metavanadate calculated as vanadium element is 0.5-5:1, more preferably 0.8-1.2:1; Preferably, in step (1), H + The molar amount of the acid in terms of OH - The molar amounts of the bases are equal.
7. The method according to claim 5 or 6, wherein: In step (1), the acid is provided by an aqueous solution of the acid, and the concentration of the aqueous solution of the acid is 0.5-4 mol / L, preferably 1-3 mol / L; Preferably, the amount of the acid aqueous solution is 200-800 mL, more preferably 350-700 mL, relative to 1 mol of the bismuth source calculated as bismuth element; Preferably, in step (1), the base is provided by an aqueous solution of base, and the concentration of the aqueous solution of base is 0.5-4 mol / L, preferably 1-3 mol / L; Preferably, the amount of the aqueous solution of the alkali is 200-800 mL, more preferably 350-700 mL, relative to 1 mol of the metavanadate calculated as vanadium element; Preferably, in step (1), the acid is selected from at least one of nitric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid and hydrochloric acid; Preferably, in step (1), the base is an alkali metal hydroxide, preferably sodium hydroxide and / or potassium hydroxide; Preferably, in step (1), the bismuth source is a bismuth-containing compound, preferably at least one selected from bismuth nitrate, bismuth trichloride and bismuth subsalicylate; Preferably, in step (1), the metavanadate is selected from at least one of sodium metavanadate, potassium metavanadate and ammonium metavanadate.
8. The method according to any one of claims 5 to 7, wherein: Step (1) comprises: adding the mixed solution A containing the bismuth source and the acid to the mixed solution B containing the metavanadate and the alkali under stirring to carry out a contact reaction; Preferably, the addition rate of the mixed solution A containing the bismuth source and the acid is 0.5-5 mL / min relative to 10 mL of the mixed solution B containing the metavanadate and the base; Preferably, in step (1), the contact reaction conditions include: temperature of room temperature-80°C, and time of 0.5-24h.
9. The method according to any one of claims 5 to 8, wherein: In step (2), the titanium source is a titanium-containing compound, preferably at least one selected from tetrabutyl titanate, titanium sulfate and titanium tetrachloride; Preferably, in step (2), the solvent is an alcohol, preferably a monohydric alcohol and / or a polyhydric alcohol, more preferably at least one of a C1-C10 monohydric alcohol, a dihydric alcohol and a trihydric alcohol, preferably at least one of ethanol, ethylene glycol, n-propanol, isopropanol, 1,2-propylene glycol, 1,3-propylene glycol and glycerol, more preferably at least one of ethanol, isopropanol and glycerol; Preferably, in step (2), the conditions of the solvent thermal reaction include: temperature of 90-200° C. and time of 12-48 h.
10. The method according to any one of claims 5 to 9, wherein: In step (3), the active metal is selected from iron and / or cobalt and ruthenium; Preferably, in step (3), the active metal precursor is selected from soluble compounds of each active metal, preferably at least one selected from nitrates, chlorides and sulfates of each active metal; Preferably, in step (3), the mixing is mechanical mixing and / or rotary evaporation drying, and more preferably rotary evaporation drying; Preferably, in step (3), the conditions for the rotary evaporation drying include: a temperature of 70-90°C.
11. The method according to any one of claims 5 to 10, wherein: In step (3), the calcination conditions include: temperature of 350-600°C, time of 2-8h, and heating rate of 2-10°C / min; Preferably, the flow rate of the reducing atmosphere is 10-80 mL / min, more preferably 20-60 mL / min; Preferably, the reducing atmosphere comprises H2 and optionally an inert gas; Preferably, based on the total volume of the reducing atmosphere, the content of H2 is 5-100 volume %, more preferably 10-50 volume %.
12. The ternary composite catalytic material obtained by the preparation method according to any one of claims 5 to 11.
13. Use of the ternary composite catalytic material according to any one of claims 1 to 4 and 12 in a photocatalytic ammonia decomposition hydrogen production reaction.
Citation Information
Patent Citations
Preparation method of graphene-titanium dioxide-bismuth vanadate photocatalytic functional fabric
CN110387737A
Preparation method and application of gold nanoparticle regulated ultrathin two-dimensional metal phthalocyanine / bismuth vanadate heterojunction photocatalyst
CN112473747A
Efficient photocatalyst for bismuth vanadate nanorod and preparation method of catalyst
CN104014326A
Preparation method Ag-TiO2 / BiVO4 ternary photocatalyst
CN106140158A
Preparation method of bismuth vanadate / titania composite photocatalytic material
CN107890864A